Discussing Concepts of Terrorist Rationality: Implications for Counter-Terrorism Policy - Eric van Um (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Scholars of terrorism studies have long struggled to agree on a common understanding of what terrorism is. To date, they have agreed on little more than the fact that terrorism is difficult to define. As a consequence, more than 100, if not more than 200 modern definitions of terrorism have been formulated. Within those definitions, different aspects of terrorism are stressed including the underlying motivations, applied tactics and chosen targets. While no consensus has been found on how to define terrorism or terrorists, a meta-study by Schmid and Jongman (1988) provides fruitful insight into the most relevant aspects of definitions of terrorism which have proven valid to the present day. The two researchers analyzed various academic and official definitions of terrorism and identified three main elements as being vital to define terrorism; (1) the use (or threat) of violence1, (2) political objectives and (3) the intention of sowing fear in a target population as a means of achieving these political objectives.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330